2019
DOI: 10.3389/fpsyg.2019.01888
|View full text |Cite
|
Sign up to set email alerts
|

How Does Exercise Improve Implicit Emotion Regulation Ability: Preliminary Evidence of Mind-Body Exercise Intervention Combined With Aerobic Jogging and Mindfulness-Based Yoga

Abstract: Purpose: The primary aim of the present study is to examine the effect of 8-week mind-body exercise intervention combining aerobic jogging and mindfulness-based yoga on implicit emotion regulation ability. The secondary aim is to explore the specific potential pathways by which the mind-body exercise intervention fosters implicit emotion regulation. This may help us to understand how the key components of exercise intervention contribute to emotional benefits. Methods: Sixty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…A large population-based, cross-sectional study in South Korea found that those who did not report involvement in physical activity over the past year were more likely to report suicidal thoughts [ 63 ]. It is well known that acute aerobic exercise improves emotional regulation by improving the ability to attenuate negative emotions [ 17 ], enhancing resilience when dealing with life’s stressors [ 67 ]. Thus, exercise shows potential as an adjunctive treatment for people experiencing suicidal thoughts and should be investigated in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large population-based, cross-sectional study in South Korea found that those who did not report involvement in physical activity over the past year were more likely to report suicidal thoughts [ 63 ]. It is well known that acute aerobic exercise improves emotional regulation by improving the ability to attenuate negative emotions [ 17 ], enhancing resilience when dealing with life’s stressors [ 67 ]. Thus, exercise shows potential as an adjunctive treatment for people experiencing suicidal thoughts and should be investigated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, aerobic exercise is also known to enhance the ability to regulate emotions through increasing executive function. In a randomized control trial, acute aerobic exercise increased the capacity to downregulate negative emotions in response to unpleasant emotional cues [ 17 ]. Regarding suicide attempts, a case-controlled study showed an independent protective association between physical activity and the risk of suicide attempts [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feeling or mood, which is an important variable that can determine whether an individual continues or quits exercising [4], is highly influenced by various senses that are perceived while exercising [7]. If the exercise environment is comfortable, people's physical and psychological state will be positive, maximizing the effects of exercising and enabling them to continue exercising [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a need to analyze the reasons behind why over 50% of participants quit exercising after approximately 6 months despite the psychological benefits [3]. The reasons may be attributable to various personal factors, social factors, exercise programs, and so on; however, the feelings or mood that is experienced during exercise may be a prominent issue [4]. In general, an individual's feelings are closely related to one's sense of happiness, how they address stressful situations, and quality of life [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The role of aerobic fitness in particular is further underlined in an experimental study that focused on emotion regulation. After 8 wk of an exercise program that included aerobic exercise and yoga, gains in aerobic fitness mediated the social cognition benefits of the intervention ( 49 ).…”
Section: Behavioral Effects Of Exercise On Social Cognitionmentioning
confidence: 99%